2018
DOI: 10.3390/f9020091
|View full text |Cite
|
Sign up to set email alerts
|

Drought Impact on Phenology and Green Biomass Production of Alpine Mountain Forest—Case Study of South Tyrol 2001–2012 Inspected with MODIS Time Series

Abstract: Ecological balance and biodiversity of the alpine forest is endangered by global and local climatic extremes. It spurs a need for comprehensive forest monitoring, including in depth analyses of drought impact on the alpine woodland ecosystems. Addressing an arising knowledge gap, we identified and analyzed 2002-2012 aridity related responses within the alpine mountain forest of South Tyrol. The study exploited a S-mode PCA (Principal Component Analysis) based synergy between meteorological conditions rendered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
1
9
1
Order By: Relevance
“…Our result is further in line with the advancing trend direction, albeit with different strength, reported by Vitasse et al (2018), where the average spring leaf-out dates significantly advanced by about 0.22 d yr −1 across all species and sites in the Swiss Alps over the period 1980-2016. However, this finding is in disagreement with reports from Xie et al (2017) and Lewinska et al (2018), where SOS showed no significant trends between 2003 and 2014 as well as between 2001 and 2012. However, the length of the observation period may strongly affect the strength and direction of a detected trend (Mudelsee, 2019).…”
Section: Regional and Elevational Variation Of The Annual Trend Of Socontrasting
confidence: 99%
“…Our result is further in line with the advancing trend direction, albeit with different strength, reported by Vitasse et al (2018), where the average spring leaf-out dates significantly advanced by about 0.22 d yr −1 across all species and sites in the Swiss Alps over the period 1980-2016. However, this finding is in disagreement with reports from Xie et al (2017) and Lewinska et al (2018), where SOS showed no significant trends between 2003 and 2014 as well as between 2001 and 2012. However, the length of the observation period may strongly affect the strength and direction of a detected trend (Mudelsee, 2019).…”
Section: Regional and Elevational Variation Of The Annual Trend Of Socontrasting
confidence: 99%
“…Also, the expected influence of exposition on snow and vegetation phenology is not traceable in the data set. The fact that the investigated metrics did not vary depending on HLI might indicate that the used spatial resolution of 250 m is still too coarse to capture habitat differences that are created by small-scale topographic variations, a shortcoming that was also detected in a study using similar data [111]. As discussed by Comola et al [112], the effect of aspects become uncorrelated and orientation differences average out at larger scales.…”
Section: Assessment Of Spatiotemporal Patterns Of Snow and Vegetationmentioning
confidence: 90%
“…Mountain ecosystems in the European Alps have been increasingly affected by drought events in recent years (Conedera et al, 2006;Fink et al, 2004;Gobiet et al, 2014;Lewińska et al, 2018). Due to changing climatic conditions, the Alps are vulnerable to deviations in water cycling, which is mainly observed in the context of natural vegetation and agricultural activities.…”
Section: Introductionmentioning
confidence: 99%